ASSESMENT MODEL OF NAVAL WARSHIP (KRI) READINESS TO SUPPORT MAIN TASK OF THE NAVY - Prasetia, Heru; Wirjodirjo, Budisantoso; Hartoko, Priyadi (JOURNAL ASRO, 2021)
KRI is a representation of the strength and ability of the Indonesian Navy in maintaining state sovereignty in the maritime jurisdictional area. The complexity of the threat in the area of operation will determine the amount, type and level of readiness of the KRI that will carry out the operation. Therefore, information on the level of readiness of the KRI "Ready for Combat", "Ready for Operation" or "Not Ready" is very important for Sops as a basis for selecting the KRI for carrying out operations. The purpose of this research is to create a model of KRI readiness assessment that is relevant to current conditions and according to the needs of the organization. In this study using the Analytical Network Process (ANP) method to determine the weight of the assessment criteria including technical ability, spare parts, ammunition, personnel and glagaspur. Furthermore, in the calculation using the direct measurement method. The results of weighting data processing using the Analytic Network Process (ANP) show that the technical ability with a value of 0.359, spare parts 0.053, ammunition 0.034, personnel 0.113, and glagaspur 0.441. In the assessment of KRI HBS-382, it was found that KRI HBS-382 had readiness at the level of "ready for operation" with a value of 71.1%, while the assessment on KRI REM-331 has a readiness level of "not ready" even though the final value is 79.3%, this is because the ammunition criteria are "not ready" with a value of 59.9. The results of the study, it can be concluded that the KRI readiness assessment model can be used to assess all types of KRI. This readiness assessment model has several advantages that the old assessment model does not have, including making it easier for the KRI to measure and determine the level of readiness of the KRI, making it easier for Sops to determine the amount and type of KRI for operations as needed, and Logistic community oversight in planning maintenance, repair, and overhaul (MRO). Keywords: Marine security operations, Readiness, (ANP), Assessment.